The Dead Sea Scrolls dan Sumbangsihnya terhadap Kanon Perjanian Lama - Fati Aro Zega (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
Many have attacked the inerrancy and infability of the Bible. Inherence which means free from defects, in writing and infability means infallibility, in the teachings, which conservative evangelicals hold firm to the Bible, are always under attack and accusations, that the Bible is no longer authentic. Through descriptive qualitative methods with library studies, it can be concluded that there is a role of archeology and the dating of dead sea scrolls so that in the Qumran Old Testament, which is approximately 2,200 years old, it adds one manuscript evidence about the authenticity of copying. The Scriptures of no religion have documentary evidence like this. More importantly, the contribution of The Dead Sea Scrolls is evident through the acknowledgment of the world of critical scholarship which must undeniably admit that the events of Jesus are historical events, not as they have been about